2012
DOI: 10.1176/appi.focus.10.2.231
|View full text |Cite
|
Sign up to set email alerts
|

Risperidone Nonadherence and Return of Positive Symptoms in the Early Course of Schizophrenia

Abstract: Objective-This study examined the effect of medication nonadherence on the return of positive symptoms among recent-onset schizophrenia patients.Method-Three sets of operational criteria for medication nonadherence with differing levels of severity were compared for their ability to predict relapse. Explicit operational criteria are provided with the hope that they will be adopted by others. Psychotic symptoms were prospectively rated on a frequent basis, and systematic criteria were applied using a computer s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…injectable fluphenazine (Prolixin) decanoate, during most or all of the study period. This raises the possibility that adherence to a consistent type and dose of medication might “trump” some of the usual demographic and premorbid adjustment predictors found in the literature because one of the strongest determinants of symptom remission or relapse is medication adherence (Bachmann et al, 2007; Lieberman et al, 1993; Rabiner et al, 1986; Robinson et al, 1999; Subotnik et al, 2011; Subotnik et al, in press). In addition, combining positive symptoms (including disorganization) and negative symptoms into a single category might also obscure the identification of predictors of symptom remission.…”
Section: Discussionmentioning
confidence: 99%
“…injectable fluphenazine (Prolixin) decanoate, during most or all of the study period. This raises the possibility that adherence to a consistent type and dose of medication might “trump” some of the usual demographic and premorbid adjustment predictors found in the literature because one of the strongest determinants of symptom remission or relapse is medication adherence (Bachmann et al, 2007; Lieberman et al, 1993; Rabiner et al, 1986; Robinson et al, 1999; Subotnik et al, 2011; Subotnik et al, in press). In addition, combining positive symptoms (including disorganization) and negative symptoms into a single category might also obscure the identification of predictors of symptom remission.…”
Section: Discussionmentioning
confidence: 99%
“…A study published by Robinson et al (1999b) clearly showed that despite a generally good response to initial treatment, patients with a first episode of schizophrenia had cumulative first relapse rates of more than 80% 5 years after the initial recovery. These findings have been further supported by a study published in 2011 showing that, in patients with recent-onset schizophrenia spectrum disorders, not only complete treatment discontinuation but also partial treatment nonadherence (defined as compliance to only 50-75% of a prescribed antipsychotic for two consecutive weeks or longer) was associated with a clinically relevant increased risk of relapse (Robinson, 2011;Subotnik et al, 2011). These findings have been further supported by a study published in 2011 showing that, in patients with recent-onset schizophrenia spectrum disorders, not only complete treatment discontinuation but also partial treatment nonadherence (defined as compliance to only 50-75% of a prescribed antipsychotic for two consecutive weeks or longer) was associated with a clinically relevant increased risk of relapse (Robinson, 2011;Subotnik et al, 2011).…”
Section: Why Is Treatment Continuity Needed?mentioning
confidence: 63%
“…, Subotnik et al . ). A study of medication discontinuation in 53 people that had been stable on antipsychotics for 2 years following a first episode of psychosis found that 78% experienced an exacerbation of symptoms within 1 year (Gitlin et al .…”
Section: The Effects Of Reducing or Stopping Medicationmentioning
confidence: 97%